Modelo pedagógico por competencias y su incidencia en el proceso de enseñanza aprendizaje de la Carrera de Ingeniería en Alimentos de la UTEQ, el periodo 2015-2016 - Abad Rojas, María de Lourdes (2016)
The pedagogical model undertakes the subject of focus by competencies in education, which involves withdrawing from positions functionalist and behavioral approach to constructive positions. Is raises a change in the education that is significant and that is fit to them needs of an environment that requires each time more the assessment of the knowledge and to the adaptation of new technologies of information and of communication. The idea in the present investigation is to perform an analysis of competency-based educational model and its impact on the process of teaching and learning of engineering in food of the UTEQ, in the period 2015-2016, emphasizing that under the methodology competence with regard to the requirements of the productive sector, this methodology is considered that teaching process that facilitates the transfer of knowledge , the generation of skills and abilities that allows to achieve a suitable and efficient performance to student to include all their knowledge and skills acquired in training and it can be used professionally. Competency-based educational model has an impact on the process of teaching and learning, demonstrating performance that the student has obtained once completed their educational training, highlights the growing need for educational institutions in ensuring the human and technological resources; as well as the connection between the competency-based training and its articulation with the demand of the production system.